Alternative Education Strategy in The New Normal Era: إستراتيجية التعليم البديلة في العصر العادي الجديد - Mohamad Yahya Ashari; Rifatul Mahfudhoh (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2022)
Covid 19 pandemic forces the humanbeing to change their habits and forces the teachers to innovate in their teaching. The application of approaches, methods, strategies and technics can make the students diligent in their study such as self-direct learning. The purposes of the paper are defining the strategy of Self-direct learning, the teacher role and the steps of Self-direct learning strategy. The paper uses qualitative approach by implementation of literature study and uses the procedures of miles and hubberman in data collecting and data analysis. The findings of the paper are : 1) The strategy of Self-direct learning that forces the students to upgrade the knowledge, the competence and the achievement based on personal inisiative in studying design, implementation and evaluation. 2) The strategy of Self-direct learning that forces the teacher to be the contact, supervisor and programmer in teaching. 3) The steps of Self-direct learning strategy composed of 3 (three) steps that are design, implementation and evaluation. The originality of the paper is The strategy of Self-direct learning forces the student freedom and awareness in studying. The paper type is literature study. إن جائحة كوفيد 19 شجع الناس على تحويل سلوكهم وشجع المدرسين على الابتكار في عملية التعليم بالغرفة الدراسية. فتطبيق عدة مداخل وطرائق واسترتيجيات وتكنيكات يجعل الطلاب نشيطين في التعلم منها إستراتيجية التعليم الموجه ذاتيا. اتجهت الدراسة إلى البحث عن تعريف إستراتيجية التعليم الموجه ذاتيا ودور المدرس فيها وخطواتها في التعليم. وأصبح نوع الدراسة دراسة مكتبية نظرية، فاستخدمت الدراسة مدخل البحث الكيفي مع تطبيق منهج الدراسة المكتبية واستخدمت منهج ميلس وهوبرمان في جمع وتحليل البيانات. توصلت الدراسة إلى: (1) إن استراتيجية التعليم الموجه ذاتيا هي التي تشجع الطلاب على تنمية المعرفة والمهارة والانجاز مؤسسة على المبادرة الشخصية في تصميم التعلم وتنظيم تنفيذه وتقويمه. و(2) إن استراتيجية التعليم الموجه ذاتيا تشجع المدرس على أن يكون متصلا ومرشدا ومنظما في التعليم. و(3) إن خطوات استراتيجية التعليم الموجه ذاتيا تكونت من 3 (ثلاث) خطوات، منها: التصميم والتنفيذ والملاحظة والتقويم. الاستفادة من هذه الدراسة بأن استراتيجية التعليم الموجه ذاتيا شجعت الطلاب على الدراية والاستقلال في التعلم.